PENGEMBANGAN BAHAN AJAR DENGAN PENDEKATAN CTL PADA MATERI ORGAN TUBUH MANUSIA DAN HEWAN UNTUK KELAS V SD - Elsy Melia Syari (Ensiklopedia Education Review, 2019)
Learning resources used in elementary schools in the form of textbooks are designed only to emphasize the delivery of knowledge so that it is less understood by students. Submission of material in the form of a long description makes learning not meaningful, because students are more interested in images than long descriptions. This study aims to develop teaching materials with a valid, practical and effective Contextual Teaching and Learning (CTL) approach used in the learning process. This type of research is development research. Teaching material with the CTL approach was developed using the 4D model. This model consists of 4 stages namely define, design, develop, and disseminate. The define stage is analyzing the curricurulum and analyzing students. At the design stage, the design of teaching materials is carried out using the CTL approach. At the develop stage the design of teaching materials with the CTL approach is validated by 6 validators. After the teaching materials with the CTL approach have been validated, a limited trial is then carried out. The limited test was carried out for 30 students of SDN 21 Sikapak Barat class V. The disseminate stage was not conducted. Based on the results of research conducted in the know that teaching materials with the CTL approach to the material of human and animal organs for elementary school class V declared valid by 6 validators. Based on limited trials, it is known that the use of teaching materials with the CTL approach is very practical for both teachers and students. Based on observations of activities, students are very active in the learning process. Student learning outcomes exceed the minimum limit. The conclusion of the study was that the teaching material with the CTL approach was declared valid with an average of 3.51, the teaching material was declared practical with an average of 93.43%, and the teaching material was declared effective with an average of 88.58%.